Pengaruh Harga terhadap Keputusan Pembelian pada Kosmetik Ms Glow - Mochammad Gilang Ramadhan; Diana Ramadhani; Ayu Margareta; Didit Darmawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The cosmetics industry in Indonesia is experiencing rapid progress, with the emergence of more and more products on the market, both from domestic and foreign brands. Public awareness, especially among men and women, of the importance of maintaining their appearance through the use of cosmetic products is growing. This study aims to analyze the impact of price on purchasing decisions for MS Glow products, by considering the variables of perceived quality, brand loyalty, and competitiveness in the market. The method applied is qualitative research with a literature study approach, which includes analysis of various relevant scientific literature. The results of the study indicate that price, product quality, and promotion have a significant impact on purchasing decisions. This study also highlights the importance of understanding the elements of the marketing mix, especially price, in influencing consumer purchasing decisions. These findings are expected to provide strategic recommendations to cosmetic industry players in formulating effective pricing policies that are oriented towards consumer needs.